Algorithm-Based Pediatric Otolaryngology Management During the COVID-19 Global Pandemic: A Children's Hospital of Philadelphia Clinical Consensus. (July 2020) - Chorney, Stephen R.; Elden, Lisa M.; Giordano, Terri; Kazahaya, Ken; Rizzi, Mark D.; Zur, Karen B.; Dedhia, Kavita
Objective: The coronavirus disease 2019 (COVID-19) pandemic requires clinicians to explore alternatives to routine patient management. Otolaryngologists caring for children commonly depend on physical examination, laboratory data, and ambulatory surgical procedures. Limiting patient care, mindful allocation of resources, and concern for safety have challenged all aspects of our health care system. This evidence-based clinical consensus is designed to guide practitioners of pediatric otolaryngology for common scenarios during this time. Data Sources: Peer-reviewed literature, published reports, institutional guidelines, and expert consensus. Review Methods: A clinical consensus on 6 common scenarios in pediatric otolaryngology developed with evidence-based strategies. Conclusions: Providers should suspend all in-person nonessential office visits and elective surgical procedures. An emphasis on medical management and caregiver education will provide reasonable approaches to many of the common outpatient concerns. Surgery for chronic otitis media, obstructive sleep apnea, and acute rhinosinusitis should occur only in response to severe complications or failure of medical regimens. The approach to the pediatric neck mass focuses on timely management for oncologic etiologies and cautious surgical intervention for abscess drainage or tissue sampling. Finally, epistaxis and otorrhea must be triaged and addressed without the usual ambulatory procedures. Implications for Practice: Adaptation of practice patterns during this unprecedented moment for our health care system requires thoughtful planning. The strategies described allow for safe handling of common pediatric otolaryngology diagnoses. Ultimately, otolaryngologists must be stewards of our global health community while advocating for the care of individual pediatric patients.